Metodičeskie podhody k ocenke èffektivnosti reklamy v predprinimatelʹstve v usloviâh ES - Visnevskaa, Alevtina; Rejh, Ludmila (Methodical Approaches to the Estimation of Advertising Efficiency in the Business in EU, 2005)
Successful business always has to be economically efficient. Increasing business economic efficiency with the help of advertising creates necessary conditions for business development. At the same time, advertising companies require additional financial expenditures from the company. This explains the topicality of methodical approaches to the value of advertising efficiency. The practical realization Of company's efficiency activity demands from managers the deep understanding of business efficiency, knowledge of the system of checking the economic efficiency of the company and its different kind of activities, and also the main methods increasing the economic efficiency. The questions of effective advertisement activity become important in drawing the budgets for different advertisement activities.The research shows that only 10% of firms at the Latvian market are concerned with evaluating the efficiency of advertising. Usually they are foreign firms operating at the market with a full "equipment" that allows to complete and develop their business in the existing conditions. Evaluating the efficiency of advertising is one of the most important steps in complex market research. Their experience allows to study both theoretical and practical aspects of advertising efficiency that are based on true examples and can be applied to all firms if they aim at creating a marketing strategy as a basis of their business development plans. Examples of such approaches to expenses of advertising analysis are studied in this research paper. It aims at expanding theoretical and practical knowledge to students of economics - businessmen - or managers-to-be, who will have to organize and develop their business in the framework of EU.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 487-499